Uji Aktivitas Antioksidan Ekstrak Etanol Kombinasi Daun Kersen (Muntingia calabura L.) dan Daun Kelor (Moringa oleifera L) dengan Metode DPPH (2,2-Diphenyl-1-Picrylhydrayl) - Galih Samodra; Nurul Fitri Alfathani; Peppy Octaviani (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Kersen leaves and Moringa leaves are natural sources of antioxidants that can prevent oxidative damage to the body due to free radicals. The purpose of this study was to determine the antioxidant activity of a single form and a combination of cherry leaf extract and Moringa leaf in fighting free radicals. The antioxidant activity test in this study used the DPPH method (2,2-diphenyl-1-picrylhydrazil). The results showed that ethanol extracts of single forms of cherry leaves and Moringa leaves have very strong antioxidant activity with IC50 values of 8.04 ppm and strong 68.40 ppm. The combination with a ratio of 2:1 obtained the lowest IC50 value, which is 6.35 ppm. It can be concluded that the highest antioxidant activity is found in the combination of ethanol extract of cherry leaves and Moringa leaves in a ratio of 2:1, with IC50 smaller than the single form.